A conservative transnasal endoscopic and intraoral approach in a case of a maxillary dentigerous cyst. (3rd September 2019) - Consolo, U.; Bellini, P.; Mattioli, F.; Lizio, G.
Abstract: The transoral approach for enucleation of a voluminous odontogenic lesion involving the maxillary sinus is considerably invasive and can cause irreversible damage to the ciliated mucosa with definitive loss of the normal bone morphology. Functional endoscopic sinus surgery (FESS), which increases the patency of the osteomeatal complex (OMC), involves the use of a direct approach to the lesion, facilitating the drainage of secretions and improving the ventilation. Nevertheless, FESS cannot completely enucleate large odontogenic cystic lesions, particularly dentigerous cysts associated with dislocated teeth. Accordingly, a combined transnasal endoscopic and transoral approach is desirable. Here, we report the successful use of FESS combined with a conservative intraoral approach for the treatment of a voluminous dentigerous cyst that completely occupied the maxillary sinus. In a single surgery, FESS was used to enlarge OMC and open the cystic compartment into the nasal cavity, while an intraoral approach involving the removal of a bony lid from the anterolateral wall of the maxillary sinus facilitated minimal removal of the cystic wall associated with the dislocated tooth. The bony lid was repositioned and fixed with titanium plates. Computed tomography performed at 6 months showed that the original cystic compartment, which maintained communication with the nasal cavity through the enlarged OMC, was absent, and that the sinus had recovered its healthy morphology. Computed tomography at 27 months showed the maintenance of this status with no signs of recurrence. We recommend this approach to eradicate such pathology while preserving the sinus structure and function.